Impact of Management Practices on Coffee-Pine Agroforestry: Coffee Yield and Soil Respiration - Eka Novia Rosalynda; Cahyo Prayogo; Didik Suprayogo (The University of Lampung, 2025)
The coffee-pine agroforestry system offers a promising solution to enhance coffee yields and maintain soil health on degraded lands. This study aims to evaluate the impact of various agroforestry management practices on coffee yield and soil respiration. The experiment was conducted using a complete randomized block design across five management treatments: without management, without fertilization, organic fertilization, mixed fertilization, and recommended management by Perhutani. The observed parameters included coffee yield, soil respiration, soil moisture, soil temperature, litter biomass, canopy cover, and soil organic carbon (SOC) content. Results indicated that the recommended management (RM) plot achieved the highest coffee yield (834 kg ha⁻¹), attributed to wider planting spacing, which reduced resource competition between coffee and pine trees. The RM plot also displayed stable soil moisture and temperature, supporting coffee growth. Meanwhile, soil respiration showed no significant differences across treatments, though the mixed fertilization (MF) plot exhibited the highest respiration rate, indicating higher microbial activity due to combined fertilizer use. In conclusion, optimal management in agroforestry systems can enhance coffee productivity while preserving soil health. Keywords: Agroforestry, Coffee Yield, Soil Management, Soil Moisture, Soil Respiration.